1970
DOI: 10.1139/v70-404
|View full text |Cite
|
Sign up to set email alerts
|

Partial molal volume behavior of tetraalkylammonium chlorides in aqueous acetone and aqueous dimethylsulfoxide

Abstract: The partial molal volumes of a series of tetraalkylammonium chlorides in aqueous acetone and aqueous dimethylsulfoxide at 25.000 "C are reported as a function of solvent composition. It is shown that for each solvent composition the partial niolal volume data are better represented by a quadratic in solute molecular weight than by the linear expression previously employed in similar studies. Extrapolation of molecular partial molal volumes to zero cation molecular weight has permitted evaluation of the partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

1970
1970
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 6 publications
1
11
0
1
Order By: Relevance
“…On the other hand, the slope, S v shows that the ionion interactions. In generally, S v is positive, but it can be negative for some electrolytes; particularly for tetraalkylammonium salts [52][53][54], and also have been observed in this work, values of V m 1 , S v and B v for the ILs + DMSO systems were obtained at various temperatures by a linear regression analysis, and the results are listed in Table 4 along with their the standard deviations. It was found that the apparent molar volumes at infinite dilution, V m 1 for the ILs increase with the increase in the methyl group in the cation/ anion part of ILs at a particular temperature.…”
Section: Apparent Molar Volumessupporting
confidence: 67%
“…On the other hand, the slope, S v shows that the ionion interactions. In generally, S v is positive, but it can be negative for some electrolytes; particularly for tetraalkylammonium salts [52][53][54], and also have been observed in this work, values of V m 1 , S v and B v for the ILs + DMSO systems were obtained at various temperatures by a linear regression analysis, and the results are listed in Table 4 along with their the standard deviations. It was found that the apparent molar volumes at infinite dilution, V m 1 for the ILs increase with the increase in the methyl group in the cation/ anion part of ILs at a particular temperature.…”
Section: Apparent Molar Volumessupporting
confidence: 67%
“…Various researchers have seen a shift in f 0 v with different concentrations of other solvents in water in the case of electrolytes. [23][24][25] The S v values of LiCl are negative in water and methanol mixtures at 50% methanol indicating some ion-ion interactions shown in Table 4. Similarly, the S v values of LiBr are negative in water and methanol mixtures at 40% and 50% methanol and LiI shows it negative at 40, 50, 60% methanol indicating ion-ion interactions.…”
Section: Resultsmentioning
confidence: 99%
“…S v indicates the ion-ion interactions. In the concentration range studied, S v is generally positive but may be negative for some electrolytes, particularly for tetraalkylammonium salts [28][29][30]. B v describes deviation from Debye-Hückel limiting law (DHLL), which can be understood in terms of interactions among ion solvation shells.…”
Section: Apparent Molar Volumes and Standard Partial Molar Volumes Ofmentioning
confidence: 99%